Extracts from Vaccinium myrtillus L. fruits as a source of natural colorants: chemical characterization and incorporation in yogurts - Pires, Tânia C.S. (2018)
The food industry is always seeking innovative approaches to maintain consumers’ interest and increase their awareness towards the healthiness of diets. Therefore, much interest has been given to natural food additives, namely colourants. In this work, a bilberry extract was primarily characterized in terms of anthocyanin compounds by UPLC-DAD-ESI/MSn, and its colouring capacity was further compared with a synthetic anthocyanin colourant (E163) in different yogurt formulations. The prepared samples were evaluated in different periods (0 and 7 days) for nutritional profile, individual fatty acids, soluble sugars and external colour to determine the effects of each additive. Overall, the major anthocyanin compounds in bilberry were malvidin glycoside and delphinidin glycoside derivatives. With regard to the prepared yogurts, all samples maintained the nutritional profile, individual fatty acids and soluble sugars, independent of storage time. Nonetheless, bilberry extracts showed lower colouring capacity when compared to that of E163, despite the higher stability of bilberry extract throughout the storage time, when compared to that of E163. Furthermore, another advantage of this natural extract is that it has potential bioactive properties that can be conferred to foods, due to their high content of bioactive compounds, such as anthocyanins.